Home » Aptitude » Algebra » Question
  1. If x = a (b – c), y = b (c – a) and z = c (a – b), then
    x
    3 +
    x
    3 +
    x
    3 =
    abc
    1. xyz
      3abc
    2. 3xyzabc
    3. 3xyz
      abc
    4. xyz
      abc
Correct Option: C

x
= b - c ;  
y
= b - c ;  
z
= b - c
abc

Again, b – c + c – a + a – b = 0
x
3 +
x
3 +
x
3 = ( b - c )3 + ( c - a )3 + ( c - a )3
abc

= 3 (b – c) (c – a) (a – b)
Required answer =
3xyz
abc



Your comments will be displayed only after manual approval.